FUNGSI TARI LADING DI DESA TEMPIRAI KECAMATAN PENUKAL UTARA KABUPATEN PENUKAL ABAB LEMATANG ILIR PROVINSI SUMATERA SELATAN - Rahmadini, Zakiyah; Syahrial (Greget: Jurnal Kreativitas dan Studi Tari, 2024)
The research entitled "The Function of the Lading Dance in Tempirai Village, North Penukal District, Penukal Abab Lematang Ilir Regency, South Sumatra Province", aims to describe the Form and Function of the Lading Dance. The problems in this research include: (1) what is the form of the Lading Dance? and (2) how does the Lading Dance function? Answering problems regarding dance form using Y. Sumandiyo Hadi's theory and discussing function using M. Jazuli's theory. This research uses descriptive qualitative research methods. Data obtained through observations, interviews and literature study.  The results of the research show that the form of Lading Dance is a group dance, which consists of 11 elements which include dance movements, dance space, dance accompaniment/dance music, dance theme, type/type/nature of dance, mode or method of presentation, number of dancers, gender, and body posture, make-up, lighting/stage lighting, dance props/other equipment. The functions of the Lading dance include: Lading dance for ceremonial purposes, namely the traditional wedding ceremony of Tempirai Village and the ceremony for welcoming important guests. The function of the Lading dance is for entertainment/spectacle which is intended to enliven and celebrate a meeting or reception. The function of the Lading dance for performance aims to provide an aesthetic experience to the audience. The function of Lading dance for educational media means that dance becomes a tool for education or learning the values needed to achieve goals.